Дневник свекрови: [роман] / Мария Метлицкая - Метлицкая Мария (За чужими окнами, 2017)
Экземпляры: ф.6 (20181219) / Инвентарный номер: 2339 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: М 54 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44